RAPID ISOLATION, IDENTIFICATION AND PHYLOGENETIC ANALYSIS OF PECTOBACTERIUM CAROTOVORUM ssp - Zhu, L.; Xie, H.; Chen, S.; Ma, R. (Journal of plant pathology, 2010)
Thirty-two strains of Pectobacterium carotovorum ssp. (Pec) were isolated from Chinese cabbage and other vegetables. These strains were subject to morphological observation, biochemical and physiological identification as well as 16S rDNA sequence analysis. All strains except D4, Z1-2, Z2-1, Z2-2 and Z3-2 manifested the same PCR patterns as indicated by amplifying 16S-23S rDNA ITS and ITS-RFLP. The phylogenetic analysis of the 16S rDNA sequences indicated that these five strains that clustered with Pec strain PCI and close to P. betavasculorum and P. wasabiae were distinct from other strains in the Pec groups. However, the whole-cell fatty acid analysis and the biochemical and physiological characteristics suggested that these five strains could still be identified as Pec. In conclusion, our results suggest that these five strains are probably from a new evolutionary taxonomy oí Pectobacterium carotovorum ssp.